Leaderless and leader-following consensus for heterogeneous multi-agent systems with random link failures - Kim, Jae Man; Park, Jin Bae; Choi, Yoon Ho (IET control theory & applications, 2014)
This study investigates the heterogeneous consensus problem for multi-agent systems with random link failures between each agent. The discrete-time heterogeneous multi-agent systems are described by first-order and second-order dynamics, and the communication network is assumed to be directed with fixed topology. Since each link between the agents is subject to failure with a certain probability, the control protocol is designed considering the random link failures. The random link failures are presented by a Bernoulli probability sequence, that is, the control protocol for failure occurrence is designed using the one step previous data that is sent by adjacency neighbouring agents. The control protocol for heterogeneous multi-agent systems is designed for first-order dynamics and second-order dynamics using the Lyapunov method. The mean square stability is shown for leaderless and leader-following heterogeneous multi-agent systems in terms of a set of linear matrix inequalities, and some simulation results are provided to verify the effectiveness of the proposed methods.